Study on Asymmetry Stainless Steel Filtration Membrane Used in Juice Industry. Issue 3 (March 2015) - Qiangbing, Wang; Huiping, Tang; Zhengping, Xi; Baojun, Yang; Yuan, Ge
Abstract The changes of the brix, the color values, the turbidity, and the transparency of the juice during the process of filtering juice under operating pressure were discussed. Results show that compared with the relevant physical and chemical indexes of the juice before filtering, the brix of the apple juice after filtering decreases from 15% to 14.3%, transparency (T625) is more than 80%, turbidity (NTU) is smaller than 1, and the juice color values (T440) can amount to more than 40%. The above mentioned results predict that the application of the asymmetric stainless steel filtration membrane in juice industry presents a very good potential prospect.